AI, the internet of legal things, and lawyers. Issue 4 (2nd October 2019) - Tung, Kenneth
Abstract : A great deal of has been written about the challenges of a legal profession that resists change and sub-optimizes clients' benefits, and even more ink has been spilled on the opportunities and threats of AI. As laws are falling further behind an accelerating, dynamic world, the gap between businesses and opaque legal functions widens with the latter being perceived often as fire-fighting cost centers. This article calls out the opportunity of AI, specifically machine learning, and its impact on decision making as an opportunity for business leaders to elevate lawyers to contribute further to corporate strategies and operations. Surveying the implications of machine learning through the lens of each element of decision making, the article aims to bring the relevance of today's ubiquitous transformations to the legal function. It also reminds business leaders that the legal function will need some help, such as corporate legal strategists, to drive and sustain change that resides in the intersection of law, business and technology.